2016
DOI: 10.1111/exd.13180
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of NADPH oxidase in vitro and in vivo suppresses fibroblast activation and experimental skin fibrosis

Abstract: Although there is increasing evidence that oxidative stress is involved in collagen synthesis and myofibroblast activation, the NADPH oxidase (Nox) system is incompletely investigated in the context of human dermal fibroblasts (HDFs) and skin fibrosis. Using the pan-Nox inhibitor diphenyleneiodonium (DPI) as an initial tool, we show that gene expression of collagen type I, α-smooth muscle actin (α-SMA) and fibronectin 1 is suppressed in HDFs. Detailed expression analysis of all Nox isoforms and adaptors reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Currently, a few nonspecific NOX inhibitors have been identified (which target more than one NOX isoforms) [88], [142], [143], [144], [145], [146], [147]. Some issues with specificity, potency, and toxicity of these inhibitors have limited the use of these compounds in clinical studies [148].…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a few nonspecific NOX inhibitors have been identified (which target more than one NOX isoforms) [88], [142], [143], [144], [145], [146], [147]. Some issues with specificity, potency, and toxicity of these inhibitors have limited the use of these compounds in clinical studies [148].…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 99%
“…It inhibits a number of flavoproteins including eNOS, xanthine oxidase, and cholinesterases and the internal calcium pump [150]. Although at least two pre-clinical studies using DPI have shown positive results on lung cancer inhibition [142] as well as skin fibrosis reduction [143], the off-target effects of DPI against other flavoproteins will prevent its translation into clinical use.…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 99%
“…Poldip2 is fairly ubiquitously expressed, having been reported in aorta, 3, 4 lung, 3 kidney, 3, 5, 6 heart 7 and thyroid, 8 as well as many cell types including mouse aortic smooth muscle cells, 9 astrocytes, 10 vascular smooth muscle cells (VSMC), 3, 11 brain endothelial cells, 12 epithelial cells, 12 HeLa, 1, 12-15 fibroblasts, 2, 13, 16, 17 kidney fibroblasts, 18 myoblasts, 19 human umbilical vein endothelial cells, 20 human embryonic kidney cells 293 (HEK 293), 13 MRC5 cells, 21, 22 and cortical neurons. 23 There is also evidence of Poldip2 expression in human breast cancer, 24 human breast adenocarcinoma cells 13 and human lung adenocarcinoma cells.…”
Section: Tissue Expressionmentioning
confidence: 99%
“…[10][11][12] In addition, targeting of ROS-generating NADPH oxidase in vitro and in vivo suppresses fibroblast activation and experimental skin fibrosis. 13 15,16 monocytes, 17 T lymphocytes 18 and erythrocytes. 19 Likewise, the total oxidant status of serum from SSc patients has been found to be higher with respect to control samples.…”
mentioning
confidence: 99%